STUDY OF THE "AWARENESS OF YOUNG WOMEN TOWARDS FASHION IN THE CHANGING ENVIRONMENT" IN THE CONTEXT OF MUZAFFARPUR DISTRICT - Kumari Deepmala; Kumari, Kusum; Mishra, Vidisha; Priyadarshini, Shweta; Renu Kumari; Sangeeta Rani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research presented here is related to the study of awareness of young women towards fashion in the changing environment. For this, 100 young women aged 18 to 25 years have been selected. In this, the help of interview and schedule method has been taken. Under the research, age has been considered as an important main variable among the independent variables. The social, educational and biological level of the young women included in the research has been studied. The research will prove to be helpful in making young women self-reliant and independent. Statistical analysis show that 75% of young women have a positive attitude towards fashion, and they believe that fashion has a great contribution in developing their personality.